Empowerment of Used Cooking Oil Processing in Durenjaya Village: Pemberdayaan Pengolahan Minyak Goreng Bekas di Desa Durenjaya - Khoirilia , Irsalina; Sukmana, Hendra (Indonesian Journal of Law and Economics Review, 2025)
General Background: Waste cooking oil has become a domestic environmental issue that potentially harms drainage and public health. Specific Background: In Kelurahan Durenjaya, Bekasi, household disposal practices remain high, while knowledge of alternative reuse is still limited. Knowledge Gap: Previous community services rarely focused on converting cooking oil into eco-friendly products through systematic training in local neighborhoods. Aims: This paper reports a community empowerment program that provides education, workshops, and mentoring on producing aromatherapy candles from used cooking oil. Results: The program increased residents’ awareness of environmental risks and enabled them to process waste oil into value-added products. Participants showed improved skills and initial attempts at simple product marketing. Novelty: This activity integrates environmental education with practical household-based candle production in a specific urban area. Implications: The program may support sustainability efforts and create small-scale economic opportunities for households. Highlights:• Increased environmental awareness• Skills in producing aromatherapy candles• Practical reuse of domestic waste Keywords: Community Empowerment, Waste Cooking Oil, Training, Environmental Awareness, Bekasi